Imperialism: a study - Hobson, J A (Aakar books, 2017)
n his Preface to the 1902 first edition of Imperialism: A Study, imperial critic J.A. Hobson demonstrates his prophetic talents by noting, just as the Victorian age was ending and World War I was brewing, that "Imperialism has been adopted as a more or less conscious policy by several European States and threatens to break down the political isolation of the United States." Though the book speaks mostly of British imperialism of the period, Hobson invevitably explores the general principles-and hidden motives-of imperialist policy. Hobson covers: the commercial value of imperialism, imperialism as an outlet for population, economic parasites of imperialism, imperialist finance, moral and sentimental factors, and much more. With imperialism again a hot topic in the political arena, Hobsons treatise continues to lend invaluable and necessary insight into a complex ideology.